Territorial Identity of Countryside Residents in the Suburban Areas of Łódź, Poland - Wójcik, Marcin (Quaestiones Geographicae, 2013)
Social studies of suburban villages have important implications for modern human geography. To a large extent, they relate to a broader problem, which is a change in the value system of Polish society and the needs met in the countryside environment. It is worth considering how a society with specific needs changes the space of the contemporary suburban village. The knowledge of those processes is necessary to further develop spatial policies and local development of gminas (communes) in Poland, especially in the case of rapidly transforming villages in the vicinity of large cities. The primary objective of this paper is to identify differences in the territorial identity and social perception of rural space expressed by immigrant and local groups of long-term residents.